Pelagic Amphipods in the Eastern Fram Strait With Continuing Presence of Themisto compressa Based on Sediment Trap Time Series - Schröter, Franz; Havermans, Charlotte; Kraft, Angelina; Knüppel, Nadine; Beszczynska-Möller, Agnieszka; Bauerfeind, Eduard; Nöthig, Eva-Maria (Frontiers in Marine Science, 2019)
Pelagic amphipods represent a large fraction of organisms entering sediment traps as so-called “swimmers”. These swimmers were sampled with sediment traps ( ~ 200 to 300 m water depth) with two mooring arrays deployed at two different positions in the Long-Term Ecological Research observatory HAUSGARTEN in the northeastern Fram Strait. This sampling allowed us to investigate amphipod year-round abundances and inter-annual trends from 2000 onwards. In this study, newly analyzed data from a 3-years period (August 2011- June 2014) are presented, extending this long-term investigation. In our results, the species Themisto abyssorum, T. libellula and T. compressa dominated the swimmer biomass, corroborating previous studies. The observed increase of amphipod abundances persisted in all three species additionally implying that Themisto compressa maintained its population off Svalbard which appeared for the first time here after a warm anomaly in 2004-2007. This study provides evidence for changes in amphipod community patterns which can mainly be attributed to growing abundances in T. compressa. Similarly, another hyperiid, Lanceola clausii, also increased in abundance over the investigated period, since its appearance in 2003. For Themisto libellula, almost no juvenile individuals were recorded in the sampling period 2013/14, even though juveniles of this species were common in earlier records. The three more years of observations clearly suggest that recently documented environmental shifts persist in the eastern Fram Strait. They also highlight the merit of using sediment trap time series to obtain year-round data sets which are needed to reveal processes and range shift dynamics in the pelagic system on a long-term basis.